Smartphone dependence and its influence on physical and mental health - Zhu, Wei; Zhang, Ying; Lan, Yanzhi; Song, Xinqiang (Frontiers in Psychiatry, 2025)
Smartphones have become an integral part of life for an increasing number of people around the world, especially as the range and speed of smartphone functions has expanded. However, excessive use of smartphones can cause not only physical discomfort but also feelings of loneliness, anxiety, and depression. The present review explores the negative effects of excessive smartphone use on physical and mental health. It also surveys measures that can counteract these effects, which include controlling smartphone use, strengthening self-control, and engaging in physical exercise.